5(a-7)+17=2(a-6)

Simple and best practice solution for 5(a-7)+17=2(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(a-7)+17=2(a-6) equation:


Simplifying
5(a + -7) + 17 = 2(a + -6)

Reorder the terms:
5(-7 + a) + 17 = 2(a + -6)
(-7 * 5 + a * 5) + 17 = 2(a + -6)
(-35 + 5a) + 17 = 2(a + -6)

Reorder the terms:
-35 + 17 + 5a = 2(a + -6)

Combine like terms: -35 + 17 = -18
-18 + 5a = 2(a + -6)

Reorder the terms:
-18 + 5a = 2(-6 + a)
-18 + 5a = (-6 * 2 + a * 2)
-18 + 5a = (-12 + 2a)

Solving
-18 + 5a = -12 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-18 + 5a + -2a = -12 + 2a + -2a

Combine like terms: 5a + -2a = 3a
-18 + 3a = -12 + 2a + -2a

Combine like terms: 2a + -2a = 0
-18 + 3a = -12 + 0
-18 + 3a = -12

Add '18' to each side of the equation.
-18 + 18 + 3a = -12 + 18

Combine like terms: -18 + 18 = 0
0 + 3a = -12 + 18
3a = -12 + 18

Combine like terms: -12 + 18 = 6
3a = 6

Divide each side by '3'.
a = 2

Simplifying
a = 2

See similar equations:

| 5-3w=32 | | (N-6)*8=56 | | 9-x+2=3-5x+2x | | (3x-2)(4x-1)= | | w^4-4096=0 | | 5(2)-4(-12.9)= | | 2y+(-8x)=0 | | 0.66x+6=0.5x+0.25x | | -x-5y=-13 | | .6x+6=.5x+.25x | | -2c-8=-5c+4 | | 8x+3(-12.9)=-23 | | a-9=-20 | | 8-2x^2=x^2+4-7 | | 8(3+.08y)+3y=-23 | | 5/4-7/3c | | N^7=7 | | -3x+10y=1 | | 2c-8=-5c+4 | | 1/8x+3y=3 | | 5(3)-4(0)= | | x/2+5=18 | | 2x-(x+1)=-2 | | -3.7(x-5.3)-5.3(7x-2.4)=-53.35 | | 8(n+3)=9n+3-6 | | 39k^4-9k^3/4 | | 3/5(7x+11+6x) | | 8(3)+3(0)= | | (-2x+3)=25 | | -4(m+5)= | | 2+8j= | | 5x-4(0)=15 |

Equations solver categories